Um framework para construção de sistemas inteligentes de seqüenciamento da produção - Silva, Rafael Rabêlo (Universidade Federal de São Carlos, 2009)
There are many researches being developed in the Production Sequencing and Production Scheduling by the Tear team. In one of the researches focus, it has been investigated the use of simulation in cooperation with Artificial Intelligence to obtain a computer system as the solution of a reactive system in the entrance of production system. The main goal is to have a framework model to an intelligent system to help the products sequencing in the entrance of production systems. The framework should be a guide in the construction and customization of the intelligent system to be constructed.
A framework to intelligent systems construction of production sequencing
Keywords: Ciência da computação; Sequenciamento da produção; Simulação de sistemas industriais; Sistemas inteligentes; Production sequencing; Industrial systems simulation; Intelligent systems; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO